(untitled) (Research, Society and Development, 2022)
Zoophilia can make it possible to commit other more serious crimes against human beings, as domestic violence, child abuse, alcohol and animals are closely linked. The objective of this work was to describe a case of zoophilia in a dog, to report how the legal measures have been adopted and to highlight the role of the veterinarian as an adjunct to justice. At the Veterinary Hospital of the Federal University of Piauí (HVU/UFPI), in the city of Teresina, a 5-year-old male crossbred dog presented clinical signs of abdominal pain. Clinical examination revealed behavioral arousal, subconjunctival hemorrhage in the right eye, paralysis of the pelvic limbs, congested and swollen anal mucosa, laceration of the anal mucocutaneous junction with lack of sensation and the presence of fluid secretion. After examinations, analysis of exogenous reproductive material revealed the presence of human sperm. The animal was submitted to fluid therapy and medicated. 72 hours after emergency care, the animal died. Given this precedent, the HV/UFPI filed a complaint with the Specialized Environmental Police Station (DEMA) in Teresina, PI, Brazil. At the instruction hearing and at the trial of the present case, the author of the crime and his lawyer accepted the proposal for a criminal transaction, which established a penal value for the benefit of an association for the protection of animals in the state of Piauí, with a deadline for confirmation of the deposit. on the indicated account.